Peraga Mikrometer Sekrup Braille untuk Siswa Tunanetra - Iradaty, Fithri (INKLUSI, 2017)
This research was conducted with Four D Models research design with a limited test involving three blind students at MAN Maguwoharjo, a physics teacher ath the school, and several students majoring in physics education FMIPA UNY. The result of the limited test shows that the props that have been developed can be applied as a screw micrometre model and the Braille-labeled LKS can also be used as a guide in a practicum implementation. The results of the assessment of the feasibility of the developed product are reviewed regarding several aspects which are the requirements of the measuring instrument that is validity (reliable), reliable, can be used internationally, is easy to produce, and safe. In general, Braille scarp micrometre displays are suitable for blind students. Besides, blind students strongly support the existence of braille screw micrometre displays equipped with this braille LKS as it will help them more easily understand micrometre screw gauges which in general this tool is still produced only for the non-blind.[Penelitian ini menggunakan desain Four D Models, dengan uji coba terbatas melibatkan tiga orang siswa tunanetra MAN Maguwoharjo, seorang guru fisika MAN Maguwoharjo, dan beberapa mahasiswa Jurusan Pendidikan Fisika FMIPA UNY. Hasil uji coba terbatas menunjukkan bahwa produk peraga yang telah dikembangkan dapat diterapkan sebagai peraga mikrometer sekrup dan LKS berhuruf Braille juga dapat dimanfaatkan sebagai pedoman dalam pelaksanaan praktikum. Hasil penilaian kelayakan produk peraga yang dikembangkan ditinjau dari beberapa aspek yang menjadi syarat alat ukur, yaitu valid (dapat dipercaya), reliable, dapat digunakan secara internasional, mudah diproduksi, dan aman. Secara umum, peraga mikrometer sekrup Braille layak digunakan bagi siswa tunanetra. Selain itu siswa tunanetra sangat mendukung keberadaan peraga mikrometer sekrup braille yang dilengkapi dengan LKS braille ini karena akan membantu mereka lebih mudah memahami alat ukur mikrometer sekrup yang pada umumnya alat ini masih diproduksi hanya untuk orang awas.]